How molecular internal‐geometric parameters affect PB‐PEO polymersome size in aqueous solution. Issue 7 (12th November 2015) - Habel, Joachim; Ogbonna, Anayo; Larsen, Nanna; Schulte, Lars; Almdal, Kristoffer; Hélix‐Nielsen, Claus
ABSTRACT: Amphiphilic polybutadiene polyethylene oxide (PB‐PEO) is one of the best known chemistries to form stable vesicular morphologies, stated as polymersomes, in aqueous environment. Mimicking cell membranes, these structures self‐assemble in an "amphiphilic window" determined by 0.15 <  f  < 0.35 where f is the ratio between the hydrophilic block volume and the entire diblock volume. However the polymersome size distribution also depends on molecular weight ( M n ) and in order to gain insight on how f and M n together determine polymersome size, we prepared PB‐PEO diblock copolymers with different block lengths and analyzed vesicle morphology via Dynamic light scattering (DLS) and Freeze‐fracture transmission electron microscopy (FF‐TEM). We found three main regimes: high f / low M n with polymersomes of mixed diameter, high f / high M n with mainly large polymersomes and low f, with mainly small polymersomes. In the first region, the polymersomes are highly polydisperse. There is a tendency towards increased diameter with increasing f and M n . Taken together our findings can help to identify how polymersome self‐assembly can be controlled to achieve size distribution specificity alleviating the need for subsequent tuning of size via extrusion. This can pave the way for cost‐effective upscaling of polymersome production for biomedical and biomimetic applications. © 2015 Wiley Periodicals, Inc. J. Polym. Sci., Part B: Polym. Phys.2016, 54, 699–708 Abstract : The diameter size distributions of polymersomes based on polybutadiene polyethylene oxide with high f / low M n and mixed diameters, high f / high M n and mainly large diameters, and low f and mainly small diameters were measured using dynamic light scattering and freeze‐fracture transmission electron microscopy. In the last region, the poylmersomes are highly polydisperse, containing many highly varying diameters. Furthermore, there is a tendency towards increased diameter with increasing f and M n . These findings can facilitate the cost‐efficient upscaling of polymersome production.